Physical Activity in Severe Dementia Is Associated With Agitation Rather Than Cognitive Function. (20th January 2020) - Ishimaru, Daiki; Tanaka, Hiroyuki; Nagata, Yuma; Takabatake, Shinichi; Nishikawa, Takashi
Background: The authors examined associations between physical activity, cognitive function, activities of daily living, and behavioral and psychological dementia symptoms (BPSD) in severe and moderate dementia. Methods: A cross-sectional study was conducted to assess severe and moderate dementia groups according to the Clinical Dementia Rating. An actigraphy measured physical activity. Other measures included Mini-Mental State Examination, Cognitive Test for Severe Dementia, Hyogo Activities of Daily Living Scale, and Neuropsychiatric Inventory-Nursing Home. Results: Sixty-three participants were assessed (mean age = 89.3 ± 6.4). Physical activity was not associated with cognitive function among participants with severe dementia, although there was a trend-level association with cognitive function among those with moderate dementia. Physical activity was significantly associated with BPSD, specifically agitation/aggression symptoms, for participants with severe dementia, and there was a trend-level association with anxiety for participants with moderate dementia. Conclusions: Physical activity appears to be associated with BPSD among individuals in the advanced stages of dementia.